Seasonal Prevalence and Molecular Identification of Thermophilic Campylobacter from Chicken, Cattle, and Respective Drinking Water in Kajiado County, Kenya - Wanja, Daniel W.; Mbuthia, Paul G.; Aboge, Gabriel O.; Bebora, Lilly C. (International Journal of Microbiology, 2022)
Thermophilic Campylobacter species are a leading cause of human gastroenteritis throughout the world and have been implicated in reproductive disorders (abortion), mastitis, enteritis, and/or diarrhoea in livestock. A cross-sectional survey was conducted in Kajiado County to determine prevalence, seasonality, and molecular detection of thermophilic Campylobacter species (with emphasis on C. jejuni, C. coli, and other thermophilic Campylobacter species) in chicken, cattle, and respective pooled drinking water. A total of 457 samples comprising 265 cattle rectal swabs, 142 chicken cloacal swabs, and 50 trough water samples were collected from 55 randomly selected smallholder farms. Individual samples were subjected to standard techniques for isolation and biochemical tests, followed by singleplex polymerase chain reaction (sPCR) assays for identification and confirmation of genus and species. Overall, thermophilic Campylobacter prevalence was 35.4% (95% confidence interval (95% CI) = 31.0–39.8), with C. jejuni dominating at 55.6% (95% CI = 47.9–63.3%) over C. coli in all sample types. The highest thermophilic Campylobacter prevalence was observed in cloacal swabs of live chicken at 44.4% (95% CI = 36.2–52.6%), followed by rectal swabs from live cattle at 30.9% (95% CI = 25.3–36.5%). Water samples from cattle drinkers/trough were found to be contaminated at 34% (95% CI = 20.9–47.1%). The isolation rate was higher in cattle under the confinement system (44.3%) (95% CI = 36.1–52.5%) than in those under the free-roaming grazing system. Thermophilic Campylobacter species were isolated in both seasons, with higher prevalence (39.8% (95% CI = 33.6–45.9)) recorded during rainy and cold season in all sample types except for water. There was significant (P<0.05) association between season and thermophilic Campylobacter occurrence, even though there were no statistical differences in the prevalence values across the two seasons. Results of this study demonstrate that cattle, chicken, and respective drinking water harbour potentially pathogenic thermophilic campylobacters, with C. jejuni being widely distributed among farms. It is possible that seasonal variations and cattle confinement result in differences in thermophilic Campylobacter carriage. Further epidemiological and phylogenetic studies comparing distribution of thermophilic Campylobacter spp. isolates in livestock, environmental, and human samples are recommended to establish source attribution to reduce the impact of resultant diseases for the wellbeing of public and livestock.